KEANEKARAGAMAN KUPU-KUPU DI TAMAN WISATA GUNUNG MEJA KABUPATEN MANOKWARI - Rawati Panjaitan (Jurnal Natural, 2008)
This study was done to study the diversity of butterflies and its distribution in the Gunung Meja National Park. A survey was carried out using transect count or line transect and the classification of Parson was used for habitat distribution. A number of 96 species of butterflies was encountered from the Family Papilionidae, Pieridae, Lycaenidae dan Nyphalidae. Three types of habitat covered the distribution of the butterflies’ species, i.e. primer forest with 41 species, secondary forest with 83 species, and garden and house yard with 49 species. Based on the t test, there is a significant differences on the diversity of each habitat (tcount > ttable; p > 0.05).